2011
DOI: 10.1088/0957-4484/22/18/185503
|View full text |Cite
|
Sign up to set email alerts
|

CdSe(ZnS) nanocomposite luminescent high temperature sensor

Abstract: High temperature luminescence-based sensing is demonstrated by embedding colloidal CdSe(ZnS) quantum dots into a high temperature SiO(2) dielectric matrix. The nanocomposite was fabricated by a solution process method. As-prepared CdSe(ZnS) quantum dots in the nanocomposite sensor show an absorption band at a wavelength of 600 nm (2.06 eV). Photoluminescence (PL) measurements show a room temperature emission peak at 606 nm (2.04 eV). The temperature-dependent emission spectra study shows for the first time a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 28 publications
3
41
0
1
Order By: Relevance
“…29 By making use of non-linear functions such as hyperbolic tangent sigmoids, neural network approaches are particularly efficient in dealing with non-linear aspects of the inverse problem. 30,31 This is an improvement over a simple, standard least squares fit by a sigmoidal function of the spectral feature 32 required to create the non-linear temperature relationship.…”
Section: Introductionmentioning
confidence: 99%
“…29 By making use of non-linear functions such as hyperbolic tangent sigmoids, neural network approaches are particularly efficient in dealing with non-linear aspects of the inverse problem. 30,31 This is an improvement over a simple, standard least squares fit by a sigmoidal function of the spectral feature 32 required to create the non-linear temperature relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, above 4 V, the PL intensity decreases monotonically with increasing bias, tracking the decrease in EQE of the QD-LED. The correspondence between the decreasing PL intensities and EQE with applied bias identifies the change in the QD luminescence efficiency to be sufficient to explain the QD-LED roll-off behavior.Reduction of PL efficiency in QD thin films has been previously measured when QDs are heated [8], charged (Auger recombination) [9], or placed under a strong electric field [10,11]. We eliminate temperature effects on the QD PL efficiency, as measurement of the operating temperature of our QD-LEDs with an infrared camera shows a change of no more than a few degrees, which is not sufficient to affect the PL efficiency and explain the roll-off.…”
mentioning
confidence: 99%
“…And the sensitivity shown by the sensor is around 0.14 nm/°C. The wavelength shift can be explained by the fact that heat expands the crystalline of the quantum dots material and causes a change in the band gap [13], which is only decided by the properties of the quantum dots.…”
Section: Nonmagnetic and Magnetic Quantum Dots 80mentioning
confidence: 99%
“…These semiconductor nanoparticles offer several advantages including narrow fluorescence emission, tunable wavelength, relatively high quantum yield, outstanding photo stability as well as flexible photo excitation. It also has been reported that the behavior of the luminescent properties of quantum dots with temperature has suitable characteristics for application as temperature probes [10][11][12][13][14][15]. The luminescence properties, such as the excited state lifetime, emission intensity, and peak wavelength, have been proven to be good indicators of temperature.…”
Section: Introductionmentioning
confidence: 99%